Field theory analysis for wireless infrared system's error correction - Jatoi, M.A. (IEEE Computer Society, 2014)
Wireless infrared communications (WIR) is explained as the light waves propagation in free space by means of infrared radiation which exists in 400-700nm.This range corresponds to high frequency range which is useful for higher data rate applications. Therefore, wireless infrared is applied for higher data rates applications such as wireless computing, wireless video and wireless multimedia communication applications. Introduced by Gfeller, this field has grown with various link configurations, improved transmitter efficiency, improved receiver responsivity and various multiple access techniques for improved quality. Then major contribution of noise in these systems is background light, which reduces system performance. The system error can be reduced by introduction of some error removal techniques. This paper provides a brief account on field theory used for error correction in wireless infrared systems. The results are produced in terms of bit error rate (BER) and signal to noise ratio (SNR) for various bit length to show the ability of encoding and decoding algorithms. Â© 2014 IEEE.